Fuzzy multi-criteria decision making for carbon dioxide geological storage in Turkey - Deveci, Muhammet; Çetin Demirel, Nihan; John, Robert; Özcan, Ender (Elsevier, 2015)
The problem of choosing the best location for CO2 storage is a crucial and challenging multi-criteria decision problem for some companies. This study compares the performance of three fuzzy-based multi-criteria decision making (MCDM) methods, including Fuzzy TOPSIS, Fuzzy ELECTRE I and Fuzzy VIKOR for solving the carbon dioxide geological storage location selection problem in Turkey. The results show that MCDM approach is a useful tool for decision makers in the selection of potential sites for CO2 geological storage.